Intra-arterial verapamil improves functional outcomes of thrombectomy in a preclinical model of extended hyperglycemic stroke - Nasoohi, Sanaz; Alehossein, Parsa; Jorjani, Masoumeh; Brown, Candice M.; Ishrat, Tauheed (Frontiers in Pharmacology, 2023)
The abrupt hyperglycemic reperfusion following thrombectomy has been shown to harm the efficacy of the intervention in stroke patients with large vessels occlusion. Studies of ours and others have shown thioredoxin interacting protein (TXNIP) is critically involved in hyperglycemic stroke injury. We recently found verapamil ameliorates cerebrovascular toxicity of tissue plasminogen activators in hyperglycemic stroke. The present study aims to answer if verapamil exerts direct neuroprotective effects and alleviates glucose toxicity following thrombectomy in a preclinical model of hyperglycemic stroke. Primary cortical neural (PCN) cultures were exposed to hyperglycemic reperfusion following oxygen-glucose deprivation (OGD), with or without verapamil treatment. In a mice model of intraluminal stroke, animals were subjected to 4 hours middle cerebral artery occlusion (MCAO) and intravenous glucose infusion. Glucose infusion lasted one more hour at reperfusion, along with intra-arterial (i. a.) verapamil infusion. Animals were subjected to sensorimotor function tests and histological analysis of microglial phenotype at 72 hours post-stroke. According to our findings, glucose concentrations (2.5 to 20 mM) directly correlated with TXNIP expression in OGD-exposed PCN cultures. Verapamil (100 nM) effectively improved PCN cell neurite growth and reduced TXNIP expression as well as interaction with NOD-like receptor pyrin domain-containing-3 (NLRP3) inflammasome, as determined by immunoblotting and immunoprecipitation. In our mice model of extended hyperglycemic MCAO i. a. verapamil (0.5 mg/kg) could attenuate neurological deficits induced by hyperglycemic stroke. This was associated with reduced microglial proinflammatory transition. This finding encourages pertinent studies in hyperglycemic patients undergoing thrombectomy where the robust reperfusion may exacerbate glucose toxicity.